SPIRITUAL FACTORS IN SOCIETY AND SOCIAL RELATIONS - Baltabaev, Nurlan; Aliqulov, Begzod (Science technology&Digital finance, 2023)
This article provides information on the spiritual factors present in society and social relations. In addition, the concept of society, definitions of society and types of society, the process of formation of society are also described.